Pengaruh Penggunaan Media Digital Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia di Sekolah Dasar - Oktaviani Karolina Topuha; Rizal Rizal; Muhammad Aqil; Yusdin Bin M. Gagaramusu; Muhammad Fasli (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the learning outcomes of students whose learning process involves the use of digital media in Indonesian language subjects for fifth grade students of SD Inpres 2 Talise. This study used a quantitative approach with a pre-experimental design in the form of a one-group pretest-posttest design. The population in this study consisted of all fifth grade students in the 2024/2025 school year totaling 19 students. The sample used was the fifth grade of SD Inpres 2 Talise consisting of 19 students, with the sampling technique using saturated sampling. Data collection techniques include learning outcomes tests, observation sheets, interviews, and documentation. Data analysis used in this study was descriptive and inferential statistical analysis. The results showed that the average pretest score was 45.63 and the average posttest score was 79.95. Based on the results of research on the effect of using digital media on student learning outcomes in Indonesian language subjects in the fifth grade of SD Inpres 2 Talise, the researcher concluded that the use of digital media has a significant effect on student learning outcomes. This is shown by calculations using SPSS version 23, where the sig value (2-tailed) = 0.000 <0.05, so that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, which means that the use of digital media affects student learning outcomes in Indonesian language subjects for fifth grade students of SD Inpres 2 Talise.